2013
DOI: 10.1128/iai.00050-13
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Response Regulator Rrp1 Reveals Its Regulatory Role in Chitobiose Utilization and Virulence of Borrelia burgdorferi

Abstract: cLife cycle alternation between arthropod and mammals forces the Lyme disease spirochete, Borrelia burgdorferi, to adapt to different host milieus by utilizing diverse carbohydrates. Glycerol and chitobiose are abundantly present in the Ixodes tick. B. burgdorferi can utilize glycerol as a carbohydrate source for glycolysis and chitobiose to produce N-acetylglucosamine (GlcNAc), a key component of the bacterial cell wall. A recent study reported that Rrp1, a response regulator that synthesizes cyclic diguanyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
95
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 68 publications
2
95
0
Order By: Relevance
“…Since a method to assess the level of Rrp2 phosphorylation within the cell is lacking, a potential impact of DhhP on Rrp2 phosphorylation could not be examined. Therefore, we focused on regulation of BosR (43,57,66). Similar to what was seen with the levels of RpoS, the dhhP mutant failed to induce BosR production in the absence of IPTG, indicating that the loss of OspC and RpoS in the dhhP mutant was due to a defect in BosR production (Fig.…”
Section: B Burgdorferi Dhhp (Bb0619) Is a C-di-amp Phosphodiesterasementioning
confidence: 65%
See 1 more Smart Citation
“…Since a method to assess the level of Rrp2 phosphorylation within the cell is lacking, a potential impact of DhhP on Rrp2 phosphorylation could not be examined. Therefore, we focused on regulation of BosR (43,57,66). Similar to what was seen with the levels of RpoS, the dhhP mutant failed to induce BosR production in the absence of IPTG, indicating that the loss of OspC and RpoS in the dhhP mutant was due to a defect in BosR production (Fig.…”
Section: B Burgdorferi Dhhp (Bb0619) Is a C-di-amp Phosphodiesterasementioning
confidence: 65%
“…Amazingly, B. burgdorferi accomplishes these dramatic processes with its streamlined genome and limited regulatory repertoire (32). For example, in contrast to many bacteria that have numerous c-di-GMP signaling systems (33)(34)(35)(36), B. burgdorferi has only one c-di-GMP synthase (BB0419, diguanylate cyclase), and it plays an essential role in spirochetal survival in ticks as well as modulating B. burgdorferi motility and mammalian infection (37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…Glycerol is produced by some insects as well as arthropods as a cryoprotective molecule (28), whereas chitobiose (derived from chitin), a major component of the tick cuticle, is an important source of N-acetylglucosamine for cell wall synthesis of B. burgdorferi (29)(30)(31). It was found that expression of the glycerol uptake/metabolism operon glpFKD, a chitobiose transporter gene (chbC) (30,31), and several glucosamine metabolism genes is governed by Rrp1 (23,25,32). Furthermore, constitutive expression of glpFKD in the rrp1 mutant or supplementing N-acetylglucosamine in tick midguts partially rescued the rrp1 mutant's survival in ticks or its transmission to the mammalian host (23,32).…”
mentioning
confidence: 99%
“…It was found that expression of the glycerol uptake/metabolism operon glpFKD, a chitobiose transporter gene (chbC) (30,31), and several glucosamine metabolism genes is governed by Rrp1 (23,25,32). Furthermore, constitutive expression of glpFKD in the rrp1 mutant or supplementing N-acetylglucosamine in tick midguts partially rescued the rrp1 mutant's survival in ticks or its transmission to the mammalian host (23,32).…”
mentioning
confidence: 99%
“…RpoS, functioning as a global regulator, further controls the expression of numerous genes important for the enzootic cycle of B. burgdorferi (for a review, see references 2, 3, and 9). Since the first discovery of this pathway, additional factors, including BosR (10)(11)(12), BadR (13,14), DsrA (15), Rrp1 (16)(17)(18), and the posttranscriptional regulation of rpoS (19), have been identified.…”
mentioning
confidence: 99%